TRANSITIVITY ANALYSIS OF NARRATIVE TEXT “ISSUMBOSHI” IN ENGLISH TEXTBOOK - Dedeh Hayati; Rama Dwika Herdiawan; Raynesa Noor Emiliasari (Journal of Language Education (JoLE), 2022)
Abstract This study aims to identify and describe the type of transitivity that appeared in the Narrative text titled "Issumboshi" of the English textbook for Grade X Senior high published by the Ministry of Education and Culture. The method employed in this study was qualitative, and the researcher was the central instrument. The methodology utilized in critical discourse analysis (CDA), The collected data were analyzed with SFL that emphasized the transitivity system. This study is an adaptation of Nguyen (2012). To collect, categorize, tabulate, number, and compute the data. In this study, a qualitative methodology was employed, and the researcher played a crucial role. Critical discourse analysis's methodology (CDA), The collected data was analyzed with SFL which emphasizes the transitivity system. This study is based on Nguyen (2012). To gather, classify, tabulate, number, and calculate the data. The results of the study based on data analysis show that the most dominant process is Material Process which appears 56 times, The most dominant participant is an actor which appears 56 times, and the most dominant circumstance is Location which appears to consist of Place 19 times and Time 17 Times. In this story, the author describes most of the players as an actor that do several activities and actions.